You are on page 1of 8

Averaging: Theory, Definition and Issues

A large class of perturbed problems can (after a transformation) be posed in the standard
form

dx
= εF (x, θ; ε) x ∈ IRn (1)
dt

= ω(θ) + εG(x, θ; ε) θ ∈ IRm (2)
dt
where ε ¿ 1, and both F and G are 2π-periodic in θi , θ = (θ1 , ...θm ). Some authors also
pose ”standard form” as
dx
= εF (x, t; ε) x ∈ IRn x(0) = x0 (3)
dt
where F is 2π-periodic in t. The connection between the two ”standard forms” can be seen
if one rewrites (3) as the system
dx
= εF (x, θ; ε) (4)
dt

= 1 (5)
dt
For (3) define the ”average”
1 Z 2π
F̂ (x, ε) ≡ F (x, t, ε)dt (6)
2π 0
Let y satisfy the initial value problem
dy
= εF̂ (y, ε) y(0) = x0 (7)
dt
Then there are ”averaging” theorems which prove, under certain conditions,
k x(t) − y(t) k= O(ε) (8)
³ ´
1
for t = O ε
. The ”method of averaging” thus involves

a) A transformation to standard form


b) Solving the averaged equations

Transformation to Standard Form: Introductory example


Consider the problem
d
ẍ + x = εf (x, ẋ) (˙) = () (9)
dt

1
The solution of the unperturbed problem (ε = 0) is
x0 (t) = A0 cos(t + φ0 ) (10)
where A0 and φ0 are constants. We seek an exact solution of the perturbed problem using
variation of parameters based on the amplitude-phase form of the solution x0 (t):
x(t) = A(t)cos(t + φ(t)) ≡ Acosψ (11)
The assumption that x solves the sole equation (9) imposes one condition relating the two
functions A, φ. Thus, we get to impose a second condition on A, φ. The second condition
we impose on A and φ is one which guarantees
ẋ(t) = −A(t)sin(t + φ(t)) = −Asinψ , (12)
that is, a condition which makes differentiation of x appear as if A and φ were constant.
Explicitly, we are therefore imposing the condition
d
Acosψ = −Asinψ (13)
dt
Using (11)-(12) in (9), it is readily seen that

−Ȧsinψ − Aφ̇cosψ = εf (Acosψ, −Asinψ) (14)


Expanding out the second condition (13) one gets

Ȧcosψ − φ̇Asinψ = 0 (15)

Solving (14)-(15) for Ȧ and φ̇ yields


Ȧ = εF1 (A, φ, t) ≡ −ε sinψ f (Acosψ, −Asinψ) (16)
1
φ̇ = εF2 (A, φ, t) ≡ −ε cosψ f (Acosψ, −Asinψ) (17)
A
Clearly, Fk is 2π-periodic in t, thus (16)-(17) is in standard form.

Transformation of weakly nonlinear problems


Let
ẋ = A(t)x + εg(x, t) x(0) = x0 ∈ IRn (18)
n×n
where A(t) ∈ IR . This problem is said to be weakly nonlinear because the unperturbed
problem
ż = A(t)z (19)
is linear. The unperturbed problem has n linearly independent solutions zi (t), i = 1, ...n
from which a fundamental solution matrix
Ψ(t) = [z1 , ...zn ] (20)
can be formed. Furthermore, Ψ is invertible since the columns are independent. If we define
y via
x = Ψ(t)y (21)

2
and substitute (21) into (25) we get

ẋ = Ψ̇y + Ψẏ = AΨy + εg(Ψy, t) (22)

But, since Ψ̇ = AΨ and Ψ is invertible,


ẏ = ε Ψ−1 (t) g(Ψy, t) (23)

If all zi and g are T -periodic in t, the latter system is in standard form.

Transformation of strongly nonlinear problems


Let
ẋ = f (x, t) + εg(x, t, ε) x(0) = x0 ∈ IRn (24)
We say this is ”strongly nonlinear” because the unperturbed problem is nonlinear. Assume
the unperturbed problem
ẏ = f (y, t) y(0) = Z (25)
has a (explicitly) known solution
y = Y (t, Z) (26)
We then seek a solution of the perturbed problem of the form

x = Y (t, z(t)) (27)

where z(t) = (z1 (t), ...zn (t)) is some vector valued function. Substitution of this expression
into (24) yields
∂y ∂y dz
+ = f (y, t) + εg(y, t, ε) (28)
∂t ∂z dt
where " #
∂y ∂Yi
= (29)
∂z ∂Zj ij
Since
∂y
= f (y, t) (30)
∂t
this simplifies to
∂y dz
= εg(y, t, ε) (31)
∂z dt
∂y
If ∂z
is nonsingular, then
à !−1
dz ∂y
=ε g(y, t, ε) (32)
dt ∂z
may be in standard form, depending on f , g.
Example A class of problems studied by Kuzmak and Luke is the perturbed hamiltonian
problem
d
ẍ + g(x) = εf (x, ẋ) , (˙) = ( ) (33)
dt

3
This problem can be posed as the system
ẋ1 = x2 (34)
ẋ2 = −g(x1 ) + εf (x1 , x2 ) (35)
The leading problem
ẏ1 = y2 (36)
ẏ2 = −g(y1 ) (37)
is integrable. This system is Hamiltonian with the Hamiltonian H(y1 , ẏ1 ) constant and equal
to the energy E
1 Z y
H(y1 , ẏ1 ) = E = ẏ12 + V (y1 ) , V (y) = g(s) ds (38)
2
Thus, the solution is given implicitly by
Z y1 ds
t−φ= q (39)
0 2(E − V (s))

Depending on g and the initial conditions, the solution y1 (t) will be periodic with period T .
We restrict our attention to these cases.
Specifying initial conditions for (y1 , y2 ) is equivalent to specifying the values of the con-
stants E and φ. Thus, if the integral in (39) can be evaluated and inverted there are functions
Y1 , Y2 such that
y1 (t) = Y1 (t, E, φ) (40)
y2 (t) = Y2 (t, E, φ) (41)
Morever, the period of yj (in t) T is a function of E, i.e. there exists a function T̄ such that
T = T̄ (E). Explicity,
Z
ds
T̄ = q (42)
C(E) 2(E − V (s))
where C(E) is the closed curve in the (y1 , y2 )-plane corresponding to the periodic orbit with
energy E.
Since this problem is strongly nonlinear, the methods of the previous section should apply.
Here Z = (E, φ). Thus, we now impose a time dependence on Z to transform the model to
standard form. In particular,
x1 (t) = Y1 (t, E(t), φ(t)) (43)
x2 (t) = Y2 (t, E(t), φ(t)) (44)
Thus,
∂Y1 ∂Y1 ∂Y1
ẋ1 (t) = + Ė + φ̇ = Y2 (45)
∂t ∂E ∂φ
∂Y2 ∂Y2 ∂Y2
ẋ2 (t) = + Ė + φ̇ = −g(Y 1) + εf (Y1 , Y2 ) (46)
∂t ∂E ∂φ

4
Using the fact that (Y1 , Y2 ) solves the leading problem this reduces to
∂Y1 ∂Y1
Ė + φ̇ = 0 (47)
∂E ∂φ
∂Y2 ∂Y2
Ė + φ̇ = εf (Y1 , Y2 , t̃) (48)
∂E ∂φ
Solving these for Ė and φ̇ it is clear there are functions F1 and F2 such that
Ė = F1 (E, φ, t) (49)
φ̇ = F2 (E, φ, t) (50)
However, recall that Yk are periodic in t but have a period T = T̄ (E). That is, (49)-(50) are
not in standard form since the functions Fk do not have a fixed period (2π). This example
illustrates that not all variation of parameter based transformations of oscillatory problems
will yield a standard form. Here, the method of averaging cannot be applied to (49)-(50). All
is not lost, however. There are different ways to transform perturbed hamiltonian problems
to standard form using “canonical” transformations. In particular, the choice of “action” J
rather than E essentially solves the dilema. Action is defined as
Z q
J = J(E) = 2(E − V (s)) , (51)
C(E)

is a function of E and geometrically is the area enclosed by the periodic orbit. It is a long
story, but by introducing an “angle” variable Q = E 0 (J)t, it can be shown that equations
for (J, Q) analagous to (49)-(50) are in fact in standard form.

Averaging Examples

Van der Pol Equation

ẍ + ε(x2 − 1)ẋ + x = 0 (52)


Transformation to standard form via
x(t) = A(t)cos(ψ) , ψ = t + φ(t) (53)
ẋ(t) = −A(t)sin(ψ) (54)
Yields the standard form:
Ȧ = εsin(ψ)(1 − A2 cos2 (ψ))(Asin(ψ)) (55)
1
φ̇ = ε cos(ψ)(1 − A2 cos2 (ψ))(Asin(ψ)) (56)
A
Define the average notation
1 Z 2π
< ∗ >= ∗dt (57)
2π 0
and noting
< sin2 (ψ) >= 12 < sin(ψ)cos(ψ) >
1 (58)
2 2
< sin (ψ)cos (ψ) >= 8 < sin(ψ)cos3 (ψ) >= 0

5
we obtain the averaged equations
˙ ε
 = Â(4 − Â2 ) (59)
8
˙
φ̂ = 0 (60)
The solution of these eqautions will of course depend on initial conditions for A(0), φ(0). But
notice if Â(0) = 2, Â(t) = 2 for all t. Since A = Â for t = O(ε−1 ), we obtain an asymptotic
approximation to the limit cycle of the original problem, namely,
x(t) ∼ 2cos(t) t = O(ε−1 ) (61)
˙
Moreover, from the sign of the derivative  for  > 2 and  < 2 we observe the limit cycle
is stable. Though technically we have only found an asymptotic approximation the limit
cycle, the use of averaging in this manner can be formalized to proving the existence of limit
cycles for sufficiently small ε.
Mathieu Equation

ẍ + (1 + 2εcos(2t))x = 0 x(0) = a ẋ(0) = 0 (62)


This equation models oscillators that are subject to frequency modulation. Note that since
the frequency ω 2 = (1 + 2εcos(2t)) is not a function of a slow time t̃ = εt, we cannot use the
multiple scale procedures previously discussed.
Normally one might use the amplitude-phase forms
x(t) = A(t)cos(ψ) , ψ = t + φ(t) (63)
ẋ(t) = −A(t)sin(ψ) (64)
to transform the equation to a system in standard form. Here, we use the alternate form
x(t) = y1 (t)cos(t) + y2 (t)sin(t) , (65)
ẋ(t) = −y1 (t)sin(t) + y2 (t)cos(t) (66)
To transform the system to standard form, substitute (65) into (62) to obtain one equation
for ẏ1 and ẏ2 . A second equation is obtained by requiring the time derivative of the right
side of (65) to equal the right side of (66). Solving for ẏ1 and ẏ2 we obtain the standard
form:
ẏ1 = 2εsin(t)cos(2t)(y1 cos(t) + y2 sin(t)) y1 (0) = a (67)
ẏ2 = 2εcos(t)cos(2t)(y1 cos(t) + y2 sin(t)) y2 (0) = 0 (68)
The averaged equations are then
1
ŷ˙ 1 = − ŷ2 ŷ1 (0) = a (69)
2
1
ŷ˙ 2 = − ŷ1 ŷ2 (0) = 0 (70)
2
Solving these one finds
ŷ1 (t) = acosh(εt) , ŷ2 (t) = −asinh(εt) (71)

6
so that
x(t) = ŷ1 (t)cos(t) + ŷ2 (t)sin(t) + O(ε) (72)
for t = O(ε ).
−1

An Averaging Theorem

There are many many averaging theorems. Here we state and prove one taken from Verhulst
(1985). First, let
ẋ = εf (x, t) + ε2 g(x, t, ε) , x(0) = x0 ∈ IRn (73)
ẏ = εfˆ(y) , y(0) = x0 ∈ IRn (74)
where f is T -periodic in t (and T is ε-independent) and

ˆ 1ZT
f (y) = f (y, t)dt (75)
T 0
Theorem Let x, y, x0 ∈ D ⊂ IRn , t ≥ 0 and assume

(A1) f, g, ∂f
∂x
are defined, continuous and bounded by an ε-independent constant M on D×IR+ ,
(A2) f is Lipschitz continuous for x ∈ D,
(A3) y(t) is contained in a proper subset of D,

Then, x(t) − y(t) = O(ε) for t = O(ε−1 ).


Proof: Define Z t
u(x, t) = (f (x, s) − fˆ(x))ds (76)
0
Since u is T -periodic in t
Z T Z T
k u(x, t) k ≤ max k f (x, s)ds − fˆ(x)ds k (77)
t∈[0,T ] 0 0
Z T Z T
≤ max k f (x, s)ds k + max k fˆ(x)ds k (78)
t∈[0,T ] 0 t∈[0,T ] 0
≤ 2T M (79)
making u uniformly bounded on D × IR+ .
Next, define the “near-identity” transformation
x(t) = z(t) + εu(z(t), t) (80)
Since k u(x, t) k≤ 2M T uniformly, x(t) − z(t) = O(ε). Now note,
ẋ = ż + εut (z, t) + εux (z, t)ż = εf (z + εu, t) + ε2 g(z + εu, t, ε) (81)

But, since ut (z, t) = f (z, t) − fˆ(z), we find

(1 + εux )ż = εfˆ + εR (82)

7
where the remainder term R is

R = f (z + εu, t) − f (z, t) + εg(z + εu, t, ε) (83)

Since fx is uniformly bounded, so is ux and


(I + εux )−1 = I − εux + ε2 S (84)

where S is uniformly bounded on Ω = D × IR+ . Thus,

ż = ε(I − εux + ε2 S)(fˆ + R) = εfˆ(z) + εP (85)

where
P = R + ε(fˆ + R)(εS − ux ) (86)
We wish to show P = O(ε) uniformly on Ω. Since f is Lipschitz continuous and u is bounded,
there is a constant L such that

k f (z + εu, t) − f (z, t) k≤ εL k u k≤ 2εLM T (87)


Thus,
k R k≤ ε(2LM T + M ) (88)
from which we deduce R = O(ε) uniformly on Ω. Since S and ux are uniformly bounded by
some constant K ∈ IR, there is some constant C for sufficiently small ε such that
k P k≤ ε(2LM T + M ) + ε(ε + 1)K(M T + 2LM T ) ≤ εC (89)

showing P = O(ε) uniformly on Ω. Letting t̃ = εt, we then see that the equation for ż can
be written
dz
= fˆ(z) + P (90)
dt̃
Using another theorem in Verhulst (1985), any system of the form (90) with z(0) = x 0 with
P = O(ε) uniformly on Ω must then have k z − y k= O(ε) for t̃ = O(1).